The Effect of Special Compound Exercises On The Development Of Some Physical, Functional and Fundamental Skills In University Of Nehrain Football League - Mohameed, Saad; Nawfal, Moayad (Journal of Physical Education, 2018)
The Effect of Special Compound Exercises On The Development Of Some Physical, Functional and Fundamental Skills In University Of Nehrain Football LeagueThe problem of the research lies in developing the artistic and physical levels during preparation phase (skill, tactic, physical, psychological) and the development of Al Nahrain Football league. The researchers noticed great weaknesses in some physical traits and skills. The aim of the research was to design a special program of compound exercises that develops some physical, functional and fundamental skills in soccer as well as identifying the effect of these exercise on the development of some physical and functional abilities in addition to that, the researchers aimed at identifying the effect of these compound exercises on the development of fundamental skills in Al Nehrain football league. The researchers used the experimental method. The subjects were (20) students divided into two equal groups. Pretests were conducted followed by the experimental program for two months and a half. The data was collected and treated to conclude that the proposed exercises have a positive effect on the development of physical fitness components, maximum speed, agility and flexibility. Finally the research recommended using these exercises on all university football teams.Keywords:  functional and physical abilities, fundamental skills.